2022
DOI: 10.1002/ange.202200954
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Postulates: Are They Relevant for Topochemical Reactions Occurring at Elevated Temperatures?

Abstract: A rigid inositol‐derived monomer functionalized with azide and alkyne as the complementary reactive groups (CRGs) crystallized as three distinct polymorphs I–III. Despite the unsuitable orientation of CRGs in the crystals for complete polymerization, all the three polymorphs underwent regiospecific and quantitative topochemical azide–alkyne cycloaddition (TAAC) polymerization upon heating to yield three different polymorphs of 1,2,3‐triazol‐1,4‐diyl‐linked‐poly‐neo‐inositol. The molecules in these polymorphs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Topochemical reactions attract a great deal of attention in view of their greener solvent-free and catalyst-free conditions, ability to provide unique products that are not synthesizable by conventional solution-phase chemistry, high regio/stereoselectivity, and non-necessity of tedious purification steps. ,, We have popularized the topochemical azide–alkyne cycloaddition (TAAC) reaction for the synthesis of various crystalline polymers. , , We have recently shown that TAAC chemistry is feasible even in the case of internal alkynes, which are unreactive in solution-phase Cu­(I)-catalyzed azide–alkyne cycloaddition reaction . In an effort to generalize the topochemical reactivity of internal alkynes, we synthesized monomer 1 (Supporting Information, Section S2), functionalized with azide and an internal alkyne ( i -alkyne), for topochemical polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Topochemical reactions attract a great deal of attention in view of their greener solvent-free and catalyst-free conditions, ability to provide unique products that are not synthesizable by conventional solution-phase chemistry, high regio/stereoselectivity, and non-necessity of tedious purification steps. ,, We have popularized the topochemical azide–alkyne cycloaddition (TAAC) reaction for the synthesis of various crystalline polymers. , , We have recently shown that TAAC chemistry is feasible even in the case of internal alkynes, which are unreactive in solution-phase Cu­(I)-catalyzed azide–alkyne cycloaddition reaction . In an effort to generalize the topochemical reactivity of internal alkynes, we synthesized monomer 1 (Supporting Information, Section S2), functionalized with azide and an internal alkyne ( i -alkyne), for topochemical polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 There are several reports on the nonreactivity of crystals despite obeying Schmidt's criteria 49−52 and the smooth reactivity of crystals that are expected to be nonreactive based on the above criteria. 49,53−60 Topochemical reactions of such seemingly unreactive crystals, reported so far, involved small and transient molecular motions such as translation, 53,60,61 flipping, 56 conformational change, 62−65 pedal motion, 54,55,57−59 polymorph, followed by its topochemical polymerization (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the preorganizations of functional groups in the crystal lattice might not be perfect for reaction, at higher temperatures, such a topochemical reaction can also occur due to increased kinetic movement of molecules. 27 If the ester linkage motif was changed to an amide as in 1 , due to the formation of hydrogen bonds from amide groups and the reduction of lone pair repulsion between oxygen atoms on the ester groups, 28 1 preferred to ‘unfold’ the motif to form supramolecular chains resulting from the intermolecular N–H⋯O hydrogen bonding (2.15 Å, 162°). Thus, reactive functional groups between two different molecules were preorganized, giving the topochemical geometry for reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We followed a concise strategy for the synthesis of the neoinositol monomer M1 from commercially available myoinositol (Figure 2a and SI, Section 2). 47 We obtained the plate-like crystals of the monomer M1 from the methanol/ water (5:3, v/v) mixture. The monomer M1 crystallizes in the C m space group with half a molecule in the asymmetric unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%